Bioinformatics for Evolutionary Biologists - Haubold, Bernhard; Börsch-Haubold, Angelika (Springer, 2018)
Evolutionary biologists have two types of ancestors: naturalists such as Charles Darwin (1809–1892) and theoreticians such as Ronald A. Fisher (1890–1962). The intellectual descendants of these two scientists have traditionally formed quite separate tribes. However, the distinction between naturalists and theoreticians is rapidly fading these days: Many naturalists spend most of their time in front of computers analyzing their data, and quite a few theoreticians are starting to collect their own data. The reason for this coalescence between theory and experiment is that two hitherto expensive technologies have become so cheap, they are now essentially free: computing and sequencing. Computing became affordable in the early 1980s with the advent of the PC. More recently, next generation sequencing has allowed everyone to sequence the genomes of their favorite organisms. However, analyzing this data remains difficult. The difficulties are twofold: conceptual, which method should I use, and practical, how do I carry out a certain computation. The aim of this book is to help the reader overcome both difficulties. We do this by posing a series of problems. These come in two forms, paper and pencil problems, and computer problems. Our choice of concepts is centered on the analysis of sequences in an evolutionary context. The aim here is to give the reader a look under the hood of the programs applied in the computer problems. The computer problems are solved in the same environment used for decades by scientists, the UNIX command line, also known as the shell. This is available on all three major desktop operating systems, Windows, Linux, and OS-X. Like any skill worth learning, using the shell takes practice. The computer problems are designed to give the reader plenty of opportunity for that.
A Problems Approach